013 Audit of tertiary heart failure outpatient service to assess compliance with updated nice guidelines. (16th May 2012) - Pryse-Hawkins, H; Davidson, L; Fallon, L; Guha, K; Lyon, A R; Sharma, R; Vazir, A; Cowie, M R
Abstract : Background: Clinical audit provides a mechanism to review the quality of patient care, and highlight areas for further development. The National Institute of Clinical Excellence (NICE) updated the clinical guidelines for chronic heart failure (HF) in August 2010. Incorporated into this update were audit criteria, which were used to create an electronic tool to assess current outpatient management. Methods: The audit targeted patients with HF secondary to left ventricular disease attending a tertiary cardiac centre in London. After an initial pilot period using hard copy proformas, the audit was extended in electronic format to all HF clinics within the institution. This enabled the capture of demographical data, diagnosis, treatment, monitoring including heart rhythm and rate, measures of clinical follow-up, and the compliance with rehabilitation. Results: A total of 282 patients were included in the 8-month audit, of which 71% were male. The majority of patients were elderly, with a mean age of 68 years, and most lived outside of London (68%). The three commonest HF aetiologies were ischaemic heart disease (40%), idiopathic dilated cardiomyopathy (20%) and primary valvular disease (12%). Treatment demonstrated 89% correctly prescribed a β-blocker, 91% correctly prescribed an ACE-inhibitor or angiotensin receptor antagonist and 64% correctly prescribed an aldosterone antagonist. Rehabilitation questions changed after 3 months. Within the initial 155 patients, 15% were offered a rehabilitation programme. The subsequent 127 patients were audited using three questions, demonstrating that 6% were referred, and 1% were enrolled into a rehabilitation programme, and 36% were educated regarding the benefits of exercise for HF. Discussion: The experience throughout this audit was positive as it was flexible and well supported by the audit department. The electronic proforma is easily adaptable to incorporate subsequent clinical or research questions as desired. Treatment and monitoring reflect national recommendations, but rehabilitation referrals are below desired levels. A minority of patients have been referred to or enrolled in HF rehabilitation programmes reflecting poor national provision. Two-thirds of patients lived outside of London, making it impractical for them to frequently visit our hospital. Hence a hospital-based rehabilitation programme would not improve this care priority. Added questions demonstrated less than optimal numbers receive exercise education within clinic. Conclusion: This audit demonstrated that a tertiary HF service has high rates of documentation, follow-up and compliance with established medical therapies. Notably many patients did not receive cardiac rehabilitation. This may be influenced by geographical limitations and the configuration of local services. To improve patient management further, alternative strategies including tele-health and enhanced multi-disciplinary team education are currently being explored.